The role of self-efficacy beliefs and inclusive education beliefs on teacher burnout - Deanna C. Friesen; Unnati Shory; Chastine Lamoureux (Social Sciences and Humanities Open, 2023)
The present study investigated whether teachers’ beliefs about teaching & learning and their beliefs about their own teaching self-efficacy predicted occupational burnout. Sixty-two elementary teachers completed three questionnaires: the Teacher Efficacy for Inclusive Practice Questionnaire (Sharma et al., 2012), the Beliefs about Learning and Teaching Questionnaire-Revised (Glenn, 2018) and the Teacher Burnout Scale (Richmond et al., 2001). Results revealed that while self-efficacy was associated with lower burnout, greater teacher-controlled beliefs, emphasizing grades and holding entity views (i.e., beliefs that learning ability is fixed) were associated with higher burnout scores. Additionally, teachers who had both higher self-efficacy and endorsed student-centered approaches reported experiencing less burnout. This study is the first to identify teacher belief profiles that are associated with level of burnout. Results are discussed with respect to how supporting the development of inclusive beliefs and building self-efficacy may support teacher well-being.